2021
DOI: 10.1108/jhom-01-2021-0035
|View full text |Cite
|
Sign up to set email alerts
|

A framework to guide the implementation of lean management in emergency department

Abstract: PurposeThe paper aims at enriching the knowledge of the application of lean management (LM) in emergency department (ED), structuring the methodology for implementing LM projects and summarizing the relevant dimensions of LM adoption in ED.Design/methodology/approachIn accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) statement, a systematic literature review has been performed, extracting a database of 34 papers. To answer the research purpose, a descriptive and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…The existence of lean leadership is a facilitator of implementation, on the other hand, the absence or weak leadership is seen as one of the biggest barriers to LHC (Swarnakar et al, 2021;Tortorella et al, 2020). Finally, the emergency department has a high flow of patients and health professionals, it is the main gateway to the hospital and the waiting time can lead to the death of the patient (Alnajem et al, 2019;Santos et al, 2020;Tiso et al, 2021). BIJ 30,9…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The existence of lean leadership is a facilitator of implementation, on the other hand, the absence or weak leadership is seen as one of the biggest barriers to LHC (Swarnakar et al, 2021;Tortorella et al, 2020). Finally, the emergency department has a high flow of patients and health professionals, it is the main gateway to the hospital and the waiting time can lead to the death of the patient (Alnajem et al, 2019;Santos et al, 2020;Tiso et al, 2021). BIJ 30,9…”
Section: Discussionmentioning
confidence: 99%
“…Over the years, the number of publications of conceptual articles tend to stabilize, and the number of analytical papers will become more widespread. For example, conceptual (or theoretical) studies showed the main terminologies, barriers and tools, most impacted indicators after the lean implementation, such as length of stay (LOS) and patient waiting time, readiness factors, lean leaders' behaviors and created models for the implementation and sustainability of the LHC (Aij and Teunissen, 2017;Al-Balushi et al, 2014;Bruno, 2017;Hallam and Contreras, 2018;Henrique et al, 2021;Parkhi, 2019;Santos et al, 2020;Tiso et al, 2021). Analytical (practical) studies have implemented or adapted the VSM, 5S and Kaizen tools to reduce waste, even during the COVID-19 pandemic, creating and validating frameworks for specific health contexts, and confirmed in practice the leadership behaviors and readiness factors (Cardoso, 2020;Tortorella et al, 2020;Tufail et al, 2021;Vaishnavi and Suresh, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Esto genera desafíos como la ralentización en la resolución de problemas, la falta de estímulo para la innovación y la dedicación excesiva de tiempo a asuntos políticos y burocráticos en lugar de la atención al paciente (Mosadeghrad, 2014). Sin embargo, se están implementando estrategias efectivas para abordar esta burocracia, como sistemas de gestión diaria basados en el enfoque Lean, que involucran a líderes en la solución de problemas (Tiso et al, 2021). El aprendizaje en tiempo real sobre la seguridad también ayuda a identificar y resolver problemas de manera efectiva.…”
Section: Equilibrio Entre Burocracia Y Profesionalismo: Desafíos Admi...unclassified
“…The elimination of waste through continuous improvement activities is considered an essential driver to processes change (Tiso et al, 2021). In practical terms, by reducing or eliminating waste in organizational processes and activities, less the organization losses with no value-added activities, and more planed tasks are performed in a certain period of time.…”
Section: Conceptual Research Model and Hypothesesmentioning
confidence: 99%
“…Both management systems take the customer as a basis to improve processes through continuous improvements procedures and thus make them more “clean,” objective and effective. By mapping processes, the organization can identify value adding activities (and non-value ones), delays, and resources employed in the system (Tiso et al, 2021) what becomes essential to optimize continuous improvements and waste elimination practices (Klein et al, 2021a). These elements interact in the Lean System to the pursued objective of higher quality and valued activities (Al-Aomar & Hussain, 2019; Rodgers & Antony, 2019) generating effectiveness.…”
Section: Theoretical Backgroundmentioning
confidence: 99%